Project-based learning implementation with a cooperative approach on the topic of correlation analysis - Darojat, Latifah; Pratama, David (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
This study aims to explore the implementation of project-based learning (PBL) with a cooperative approach on correlation analysis material in class XII of SMA Al Islam 1 Surakarta.  In studying correlation analysis material, several problems are often found, including the lack of application skills and also the lack of student involvement in the learning process. Therefore, through this project-based learning activity, students carry out collaborative activities in compiling projects based on real data so that they can better understand the concept of correlation in depth. This study uses a qualitative method and involves 30 students who are grouped into five groups. Each group is given the task of designing and implementing a correlation analysis project between two variables using a collaborative project-based learning approach. Data were collected through observation and student project results. Furthermore, the data was analyzed using data reduction, data display, and conclusion drawing/verifying techniques. The results of the study indicate that this method is effective in providing students with an understanding of the concept of correlation analysis, collaboration skills, communication, and problem solving. The average project score is in the category of developing according to expectations to very developed. Evaluation through a questionnaire showed that 72.41% of students gave positive responses to the learning experience, such as understanding the material, the ability to work together, and data processing using Microsoft Excel. These findings support the effectiveness of project-based learning in facilitating 21st century skills. Overall, this research provides a positive contribution to education. The implementation of Project Based Learning with a cooperative approach can be an alternative effective learning models to build conceptual understanding and collaboration skills in the modern education era.